In vitro characterization and in vivo toxicity, antioxidant and immunomodulatory effect of fermented foods; Xeniji™ - Noraisyah Zulkawi; Kam Heng Ng; Rizi Zamberi; Swee Keong Yeap; Dilan Satharasinghe; Indu Bala Jaganath; Anisah Binti Jamaluddin; Sheau Wei Tan; Wan Yong Ho; Noorjahan Banu Alitheen; Kamariah Long (BMC, 2017)
Abstract Background Xeniji, produced by fermenting various types of foods with lactic acid bacteria and yeast, has been commonly consumed as functional food. However, nutrition value, bioactivities and safety of different fermented products maybe varies. Methods Organic acid and antioxidant profiles of Xeniji fermented foods were evaluated. Moreover, oral acute (5 g/kg body weight) and subchronic toxicity (0.1, 1 and 2 g/kg body weight) of Xeniji were tested on mice for 14 days and 30 days, respectively. Mortality, changes of body weight, organ weight and serum liver enzyme level were measured. Liver and spleen of mice from subchronic toxicity study were subjected to antioxidant and immunomodulation quantification. Results Xeniji was rich in β-carotene, phytonadione, polyphenol, citric acid and essential amino acids. No mortality and significant changes of body weight and serum liver enzyme level were recorded for both oral acute and subchronic toxicity studies. Antioxidant level in the liver and immunity of Xeniji treated mice were significantly upregulated in dosage dependent manner. Conclusion Xeniji is a fermented functional food that rich in nutrients that enhanced antioxidant and immunity of mice. Graphical abstract Xeniji that rich in β-carotene, phytonadione, polyphenol, citric acid and essential amino acids promote antioxidant and immunity in mice without causing toxic effect.